Modelling E-Hailing Service Consumption: The Moderating Effect Of Situational Factors - Emily, Yapp Hon Tshin (2020)
This study attempted to understand the relationship between users’ perceived value of and satisfaction in e-hailing services. It also identified whether users’ satisfaction led towards their continuance usage intention, advocacy intention and reduced switching intention of e-hailing services. Besides, situational factors consisting of users’ time availability, drivers’ characteristics, cars’ ambience, promotional incentives and alternative attractiveness functioned as moderators. The development of this study’s theoretical framework was established through the Non- Action Loyalty Model and PERVAL theory. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used to analysed the data collected. Through a sample of 493 Millennial university students, the findings revealed that perceived value specifically convenience value, economic value, sustainability value and hedonic values have a significant and positive effect on satisfaction. Also, satisfaction was positively related with continuance usage intention and advocacy intention; but negatively related with switching intention. Furthermore, the negative relationship between satisfaction and switching intention is stronger when alternative attractiveness is low. This study has successfully extended the Non-Action Loyalty Model by incorporating situational factors as moderators within the perceived value-satisfactionloyalty link. In addition, it has also validated the necessity to include sustainability value into PERVAL theory. This study also contributed several practical implications. Limitations and future research were discussed as well.